2021
DOI: 10.1371/journal.pone.0259824
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution pattern of Cryptosporidium spp. among pre-weaned diarrheic calves in the Republic of Korea

Abstract: Cryptosporidium spp. are protozoan parasites that belong to subphylum apicomplexa and cause diarrhea in humans and animals worldwide. Data on the prevalence of Cryptosporidium spp. and its subtypes among calves in the Republic of Korea (KOR) are sparse. Hence, our study aimed to investigate the prevalence and association between the age of calf and the identified Cryptosporidium spp. and to determine the genotypes/subtypes of Cryptosporidium spp. in pre-weaned calves with diarrhea in the KOR. A total of 460 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 92 publications
1
8
4
Order By: Relevance
“…The main reason for the difference is that past research has focused mainly on C. parvum , and the occurrence of other Cryptosporidium spp. has recently increased ( 29 31 , 45 , 46 ). Compared with a previous study ( 31 ), the current results showed that the occurrence of C. bovis and C. ryanae have increased noticeably in calves.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The main reason for the difference is that past research has focused mainly on C. parvum , and the occurrence of other Cryptosporidium spp. has recently increased ( 29 31 , 45 , 46 ). Compared with a previous study ( 31 ), the current results showed that the occurrence of C. bovis and C. ryanae have increased noticeably in calves.…”
Section: Discussionmentioning
confidence: 99%
“…has recently increased ( 29 31 , 45 , 46 ). Compared with a previous study ( 31 ), the current results showed that the occurrence of C. bovis and C. ryanae have increased noticeably in calves. C. bovis, C. parvum , and C. ryanae , but not C. andersoni , were detected at similar rates in pre-weaned calves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations